2013
DOI: 10.1128/mcb.00174-13
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Nonsense-Mediated RNA Decay Activates Autophagy

Abstract: Nonsense-mediated RNA decay (NMD) is an mRNA surveillance mechanism which rapidly degrades select cytoplasmic mRNAs. We and others have shown that NMD is a dynamically regulated process inhibited by amino acid deprivation, hypoxia, and other cellular stresses commonly generated by the tumor microenvironment. This inhibition of NMD can result in the accumulation of misfolded, mutated, and aggregated proteins, but how cells adapt to these aberrant proteins is unknown. Here we demonstrate that the inhibition of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(85 citation statements)
references
References 28 publications
2
82
0
1
Order By: Relevance
“…We noted that multiple ATF-4 downstream transcriptional targets (ATF-3, CHOP, the CHOP target gadd34) and transcripts important for the induction of autophagy (LC3B and ATG5 (4, 6, 7)) were upregulated in rapamycin treated eIF2α wild-type cells and not in eIF2α S51A/S51A cells (Fig 2A), despite a minimal upregulation of ATF-4 protein with rapamycin treatment (Fig 2B). …”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…We noted that multiple ATF-4 downstream transcriptional targets (ATF-3, CHOP, the CHOP target gadd34) and transcripts important for the induction of autophagy (LC3B and ATG5 (4, 6, 7)) were upregulated in rapamycin treated eIF2α wild-type cells and not in eIF2α S51A/S51A cells (Fig 2A), despite a minimal upregulation of ATF-4 protein with rapamycin treatment (Fig 2B). …”
Section: Resultsmentioning
confidence: 94%
“…The phosphorylation of eIF2α, which also occurs with amino acid deprivation as well as with endoplasmic reticulum (ER) and other cellular stresses, similarly attenuates global protein synthesis (reviewed in (3)). However, eIF2α phosphorylation also paradoxically increases the translation of select mRNAs, including the transcription factor ATF-4 which transactivates the autophagy genes LC3B and ATG5 (4-7). …”
Section: Introductionmentioning
confidence: 99%
“…For example, apoptotic-like programed cell death does not involve caspases activation, but rather an apoptosis-inducing factor. 40 Recent studies have also suggested that inhibition of NMD can lead to autophagy; 41 however, whether NMD is inhibited during distinct autophagic inductions has yet to be determined. Cell death by necrosis is yet another mechanism that involves a family of proteases, the calpains rather than caspases.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the pathway linking ER stress response to autophagy in SM1 cells appears to be independent of decreased levels of mTOR signaling. It is interesting to note that a recent study found that inhibition of nonsense-mediated mRNA decay in cells activates autophagy (50). Although the cellular pathway for the increased autophagy was not investigated, protein production from the mutant transcript may have induced ER stress and autophagy in a similar manner that overexpression of myosin heavy chain does in the SM1 cells.…”
Section: Discussionmentioning
confidence: 99%